The Territorial Brand “Sabor Serrano” and the Agro-ecologically Based Family Agroindustry in Serra Catarinense (Brazil) - Souza, Leonardo Moura de; Tecchio, Andréia; Chechi, Leticia Andrea; Cazella, Ademir Antonio (Agrociencia Uruguay, 2022)
This article aims to analyze the main criteria for granting the territorial mark Sabor Serrano (MSS) by the Intermunicipal Consortium of Serra Catarinense (CISAMA), Santa Catarina (Brazil) and its relationship with the regulation of family agroindustry with an agroecological base. MSS is the result of an organization of more than a decade inserted in a context of inter-municipal cooperation, with the purpose of solving common problems related to the valorization of products from the family agroindustry. The methodological procedure adopted was the case study through bibliographical, documental and field research. The MSS is used by 70 agribusinesses, in 702 products, having as main criterion the sanitary norms, with great potential to articulate a joint process of recognition of agroecological and artisanal products, given that several precepts of these notions are already fulfilled.